THE ROLE OF FOOD INNOVATION PIZZA ANDALIMAN IN IMPROVING TOURIST INTEREST TO LAKE TOBA - Bantors Sihombing; Lisanhot Pandiangan (Jurnal Darma Agung, 2018)
This Research entitled The Role of Food Innovation Pizza Andaliman in Improving Tourist Interest to Lake Toba (Studyat Pizza Andaliman Restaurant Balige, Kabupaten Toba Samosir) intend to reveal about the role of food innovation in improving tourist interest to visit Lake Toba, , this study was conducted at the Pizza Andaliman Restaurant Balige, Kabupaten Toba Samosir. The research metodology used was a qualitative approach. Informants in this research are the owner of izza Andaliman Restaurant, tourism official government, foreign tourist and local tourist who visit Lake Toba, Balige. Kabupaten Toba Samosir, Sumatera Utara. The result of research indicated that food innovation Pizza Andaliman has not yet the main reason for tourist to visit Lake Toba, but tourist interest to visit Lake Toba increase after know about food innovation like Pizza Andaliman